Scleroglucan : fermentative production, downstream processing and applications - Survase, Shrikant A. (Array, 2007)
Exopolysaccharides produced by a variety of microorganisms find multifarious industrial applications in foods, pharmaceutical and other industries as emulsifiers, stabilizers, binders, gelling agents, lubricants, and thickening agents. One such exopolysaccharide is scleroglucan, produced by pure culture fermentation from filamentous fungi of genus Sclerotium. The review discusses the properties, fermentative production, downstream processing and applications of scleroglucan